Pemanfaatan Pelepah Pisang Geda Desa Jejawi Sebagai Bahan Tambah Alternatif Kuat Tekan Beton - Herri Purwanto; Adiguna; Amiwarti (Siklus : Jurnal Teknik Sipil, 2022)
In its development, concrete technology has innovated a lot in the use of its materials, such as the utilization of unused material waste. Jejawi is a village area located in OKI Regency and one of the livelihoods of its residents is gardening with the produce of Geda bananas, where after harvesting the banana stems are no longer used and become waste. This study aims to determine the effect of the utilization of Geda banana midrib ash in Jejawi Village as an added material on the quality of concrete. With experimental methods carried out in the laboratory, mixing the concrete material using the SNI quality standard K.225 and then adding variations of Geda Desa Jejawi banana ash which has been burned with an average temperature of 316oC by 2%, 2.5%, and 5%. From the test results, the compressive strength of normal concrete is 225.54 kg/cm2, the compressive strength of the banana ash variation of 2% concrete is 234.76 kg/cm2, the compressive strength of the banana ash variation of 2.5% concrete is 217.19 kg/cm2, and the compressive strength of the 5% banana ash variation of concrete is 203.64 kg/cm2. From the test results, there was an increase in compressive strength in the variation of the addition of 2% banana ash from normal concrete, but it decreased in the 2.5% banana ash variation and decreased again at 5%. So it was concluded that the addition of Geda banana stem ash in Jejawi Village could be used as an additional material for the K 225 concrete mixture at the addition of 2% banana ash